The effect of post-traumatic stress disorder on refugees' parenting and their children's mental health: a cohort study - Bryant, Richard A; Edwards, Ben; Creamer, Mark; O'Donnell, Meaghan; Forbes, David; Felmingham, Kim; Silove, Derrick; Steel, Zachary; Nickerson, Angela; McFarlane, Alexander; Van Hooff, Miranda; Hadzi-Pavlovic, Dusan (My University, 2018)
This study tested the effect of refugee caregivers' previous trauma and levels of ongoing stressors on current PTSD, and in turn how this influences parenting behaviour and consequent child psychological health.
The Lancet
Keywords: Disadvantage, adversity and resilience; Families and relationships; Health and wellbeing; Migration and settlement